Effective vocational guidance as a protective factor in the development of vocational distress - Álvarez-Maestre, Dra. Annie Julieth (Gaceta Médica de Caracas, 2020)
Stress as a psychopathological syndrome shows a prevalence between 1% and 2% of the world population. The normal conditions of daily life can become a threatening agent when the individual does not have the psychological and physical resources to respond to the situation. Stress as a psychopathological syndrome shows a prevalence between 1% and 2% of the world population. The normal conditions of daily life can become a threatening agent when the individual does not have the psychological and physical resources to respond to the situation.